DSL based automatic generation of Q&A systems - Azevedo, Renato Preigschadt de (2019)
In or der to help the user to search for relevant information,Question and Answering (Q&A) Systems provide the possibility to formulate the question freely in a natural language, retrieving the most appropriate and concise answers. These systems interpret the user’s question to understand his information needs and return him the more adequate replies in a semantic sense; they do not perform a statistical word search, thus differing from the existing search engines. There are several approaches to develop and deploy Q&A Systems, making hard to choose the best way to build the system. To turn easier this process, we are proposing a way to create automatically Q&A Systems based on DSLs (Domain-specific Languages), thus allowing the setup and the validation of the Q&A System to be independent of the implementation techniques. With our proposal, we want the developers to focus on the data and contents, instead of implementation details.